THE REPUBLIC OF BELARUS RADON DANGER MAP - L. A. Chunikhin; A. L. Chekhovsky; D. N. Drozdov (Радиационная гигиена, 2017)
Radon is the major contributor to the background exposure of the population. In the world practice, the radon risk or radon potential mapping are used for the radon dose assessment.The aim of this work was a radon danger mapping of the Republic of Belarus to assess the radiation situation and determine the radon hazard critical areas.Materials and methods: The mapping is based on measured values of radon volume activity in the living rooms of different buildings on the territory of the six regions of the Republic of Belarus. We have performed more than 4000 measurements. Integral track radon radiometers based on the polymer Kodak LR-115 film were used to evaluate radon volume activity. Exposure time ranged from 90 to 120 days. The cartogram was built with using the MAPINFO software package.Results: The low levels of radon concentrations were determined in the Brest and Gomel regions, as well as in the southern districts of Minsk and south-western districts of the Mogilev region. The high levels radon concentrations were determined in some districts of the Vitebsk and Grodno regions, as well as in the north-eastern districts of the Mogilev region. About 2–5 times nonuniformity of radon distribution in settlements of the Republic was observed. The radon hazard critical areas with radon concentrations in the range of 200–400 Bq/m3 were found in some districts of the Vitebsk, Grodno and Mogilev regions.Conclusions: The radon risk map of the Republic of Belarus gives the possibility to estimate the existing radiation risk. Taking into account the low efficiency of countermeasures long after the Chernobyl accident, it is necessary to increase the level of radiation protection through the radon mitigation activities or to change the radon normative documents.